Modified base membrane, preparation method of modified base membrane, composite current collector, electrode, battery cell and electric device

By applying modified adhesive and conductive coating on the surface of the polypropylene base film body of the composite fluid-collection, a modified layer is formed, which solves the problem of weak bonding force between the metal layer and the base film layer of the PP material, and improves the charge and discharge ratio and fast charging performance of the battery cell.

CN119899420APending Publication Date: 2025-04-29JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510074677.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Among the existing composite liquids, the bonding force of the metal layer and the base film layer of the PP material is not strong, resulting in low charge and discharge ratios at the battery cell end, making it difficult to apply to fast charging scenarios.

Method used

By applying a modified adhesive slurry and conductive coating on the surface of the polypropylene base film body, an adhesive force modified region and a conductive coating area are prepared to form a modified layer to improve the bonding force and conductivity of the metal layer and the base film layer.

Benefits of technology

The bonding force and conductivity of the metal layer and the base film layer in the composite liquid collecting fluid are significantly improved, thereby improving the charge and discharge rate and fast charging performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899420A_ABST
    Figure CN119899420A_ABST
Patent Text Reader

Abstract

The invention provides a modified base membrane, a preparation method of the modified base membrane, a composite current collector, an electrode, a battery cell and an electric device. The modified base membrane comprises a base membrane body and a modified layer located on at least one side surface of the base membrane body, the modified layer comprises a binding force modified area and a conductive coating area, the coating width of the binding force modified area in the first direction is the same as that of the conductive coating area in the first direction, the coating width of the conductive coating area in the second direction is 1.5-2.5 cm, and the first direction and the second direction are parallel to the two adjacent edges of the base film body respectively; when the modified base film is used in an electrode, the projection of the active material layer on the modified layer is located in the binding power modified area, and the projection of the adapter sheet on the modified layer is located in the conductive coating area. The base film body is subjected to partition modification, so that the binding force of the metal layer and the base film layer in the composite current collector adopting the modified base film can be improved, and meanwhile, the quick charging performance of a corresponding battery cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite current collectors, and in particular to a modified base film, a method for preparing the modified base film, a composite current collector, an electrode, a battery cell and an electrical device. Background Art

[0002] As an indispensable component of lithium-ion batteries, the main function of the current collector is to collect the current generated by the active material for input and output, which is beneficial to reduce the internal resistance of the battery and improve the battery coulombic efficiency, cycle stability and rate performance. The current collector commonly used in current batteries mainly refers to metal foil (such as copper foil, aluminum foil), but it has problems such as large thickness, heavy weight and low safety. With the development of technology, composite current collectors based on polymer films have received continuous attention from the new energy industry and are gradually being tried for application.

[0003] At present, the composite current collector is based on polyethylene terephthalate (PET) or polypropylene (PP), and aluminum or copper is deposited on the surface to form a sandwich structure of "metal-polymer material-metal". Compared with pure copper foil and pure aluminum foil, it has the advantages of high specific energy, long life, low cost, and strong compatibility. The PP material used in the middle polymer layer of the composite current collector has the problem of weak bonding between the metal layer and the base film layer during coating. In addition, in the related art, in order to match the PP film, roll welding of pure metal is usually required when preparing the composite current collector. Due to the small contact area between the conventional metal foil and the composite current collector during roll welding and the thin coating thickness of the composite current collector, the charge and discharge rate of the prepared composite current collector at the battery cell end is not high, and it is difficult to use it in fast charging scenarios. Summary of the invention

[0004] Based on this, the present application provides a modified base film, a method for preparing the modified base film, a composite current collector, an electrode, a battery cell and an electrical device to improve the bonding strength between the metal layer and the base film layer in the composite current collector using the modified base film, while improving the fast charging performance of the corresponding battery cell.

[0005] The first aspect of the present application provides a modified base film, comprising:

[0006] Basement membrane body; and

[0007] A modified layer is located on at least one side surface of the base film body, the modified layer includes an adhesion modification region and a conductive coating region, the coating width of the adhesion modification region along the first direction is the same as the coating width of the conductive coating region along the first direction, the coating width of the conductive coating region along the second direction is 1.5 cm-2.5 cm, the first direction and the second direction are respectively parallel to the two adjacent edges of the base film body; when the modified base film is used in an electrode, the projection of the active material layer on the modified layer is located in the adhesion modification region, and the projection of the adapter on the modified layer is located in the conductive coating region

[0008] In some embodiments, the adhesion-modified region and two adjacent edges of the conductive coating region are connected by a connector, and the material of the connector includes at least one of aluminum oxide, titanium dioxide, silicon dioxide and zinc oxide.

[0009] In some embodiments, the adhesion-modified region comprises one or more of a binder, a curing agent, a dispersant, a coupling agent, and a lubricant;

[0010] Optionally, the mass ratio of the binder to the curing agent is (20-40):(3-7);

[0011] Optionally, the mass ratio of the binder to the dispersant is (20-40):(3-7);

[0012] Optionally, the mass ratio of the binder to the coupling agent is (20-40):(1-5);

[0013] Optionally, the mass ratio of the binder to the lubricant is (20-40):(1-5);

[0014] Optionally, the binder includes one or more of polymethyl methacrylate, carboxymethyl cellulose, modified epoxy resin, polyethylene-polypropylene copolymer and polyurethane;

[0015] Optionally, the curing agent includes one or more of N,N-dimethylformamide, polyamide, dicyandiamide and maleic anhydride;

[0016] Optionally, the dispersant includes one or more of hydroxypropyl methylcellulose, glycidyl butyl ether, polycarboxylic acid amine and polyamine polyamide salt;

[0017] Optionally, the coupling agent includes one or more of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane and vinyltriethoxysilane;

[0018] Optionally, the lubricant includes one or more of silicone oil, alkyd resin, polyvinyl alcohol and silicate.

[0019] In some embodiments, the conductive coating region comprises one or more of a base resin, a conductive filler, and an additive;

[0020] Optionally, the mass ratio of the matrix resin to the conductive filler is (20-85):(2-70);

[0021] Optionally, the mass ratio of the base resin to the auxiliary agent is (20-85):(1.5-3.5);

[0022] Optionally, the matrix resin includes one or more of thermoplastic acrylic resin, polyurethane resin, epoxy resin, polystyrene butadiene resin, silicone resin, alkyd resin and modified resins corresponding to the above resins;

[0023] Optionally, the auxiliary agent includes one or more of an initiator, a wetting agent, a defoaming agent and a coupling agent;

[0024] Optionally, the conductive filler comprises one or more mixtures of metal conductive fillers, carbon conductive fillers, non-metal conductive fillers and conductive polymer fillers;

[0025] Further optionally, the metal-based conductive filler includes one or more of Ag, Ni and Cu;

[0026] Further optionally, the carbon-based conductive filler includes one or more of carbon black, graphite, graphene, carbon nanotubes and carbon fibers;

[0027] Further optionally, the non-metallic conductive filler includes one or more of tin oxide, zinc oxide, antimony dioxide and titanium dioxide;

[0028] Further optionally, the conductive polymer filler includes one or more of polyaniline, polypyrrole, polythiophene, and poly(3,4-ethylenedioxythiophene) polystyrene sulfonate.

[0029] In some embodiments, the coating thickness of the modified layer along the third direction is 260nm-340nm, and the third direction is perpendicular to the first direction and the second direction respectively; and / or

[0030] The material of the base film body includes polypropylene.

[0031] The second aspect of the present application provides a method for preparing a modified base film, the preparation method comprising the following steps:

[0032] Coating a modified adhesive slurry on a partial area of ​​at least one side of the surface of the base film body and coating a conductive coating on a partial area to prepare an adhesion modified area and a conductive coating area respectively to form a modified layer;

[0033] Drying the base film body after forming the modified layer;

[0034] Among them, the coating width of the adhesion modified area along the first direction is the same as the coating width of the conductive coating area along the first direction, the coating width of the conductive coating area along the second direction is 1.5cm-2.5cm, and the first direction and the second direction are respectively parallel to the two adjacent edges of the base film body; when the modified base film is used in the electrode, the projection of the active material layer on the modified layer is located in the adhesion modified area, and the projection of the adapter sheet on the modified layer is located in the conductive coating area.

[0035] In some embodiments, before the step of drying the base film body after forming the modified layer, the method further comprises:

[0036] Filling bonding material between two adjacent edges of the bonding force modified region and the conductive coating region;

[0037] Optionally, the bonding material includes one or more of aluminum oxide, titanium dioxide, silicon dioxide and zinc oxide.

[0038] In some embodiments, the modified binder slurry comprises a binder, a curing agent, a dispersant, a coupling agent, a lubricant, and a solvent A;

[0039] Optionally, the binder accounts for 20%-40% by mass in the modified binder slurry;

[0040] Optionally, the mass proportion of the curing agent in the modified adhesive slurry is 3%-7%;

[0041] Optionally, the mass proportion of the dispersant in the modified binder slurry is 3%-7%;

[0042] Optionally, the coupling agent accounts for 1% to 5% by mass in the modified adhesive slurry;

[0043] Optionally, the mass proportion of the lubricant in the modified adhesive slurry is 1%-5%;

[0044] Optionally, the solvent A comprises ethylene glycol; and / or

[0045] The conductive coating comprises a base resin, a conductive filler, an additive and a solvent B;

[0046] Optionally, the mass proportion of the matrix resin in the conductive coating is 20%-85%;

[0047] Optionally, the conductive filler accounts for 2%-70% by mass in the conductive coating;

[0048] Optionally, the mass percentage of the auxiliary agent in the conductive coating is 1.5%-3.5%;

[0049] Optionally, the auxiliary agent includes one or more of an initiator, a wetting agent, a defoaming agent and a coupling agent;

[0050] Optionally, the solvent B includes one or more of toluene, ethanol, acetone, xylene, cyclohexane, cyclohexanone, ethyl acetate, n-butanol, isopropanol, dimethylformamide and butyl acetate.

[0051] In some embodiments, before the step of preparing the modified layer, the method further includes: plasma cleaning the base film body;

[0052] Optionally, the cleaning gas for plasma cleaning includes argon;

[0053] Optionally, the power of the plasma cleaning is 110W-180W;

[0054] Optionally, the plasma cleaning time is 6s-10s;

[0055] Optionally, the bias voltage of the plasma cleaning is 400V;

[0056] Optionally, the gas flow rate of the plasma cleaning is 400 sccm.

[0057] In some embodiments, the step of drying the base film body after forming the modified layer comprises:

[0058] Sequentially performing far-infrared radiation heating drying and oven drying on the base film body after forming the modified layer;

[0059] Optionally, the infrared band used in the far-infrared radiation heating drying is 3 μm-14 μm;

[0060] Optionally, the maximum power density of the far-infrared radiation heating drying is 3W / cm 2 -5W / cm 2 ;

[0061] Optionally, the drying time of the far-infrared radiation heating drying is 1 min-3 min;

[0062] Optionally, the oven drying temperature is 60°C-100°C;

[0063] Optionally, the oven drying time is 1 min-3 min.

[0064] The third aspect of the present application provides a composite current collector, comprising a modified base film and a metal layer located on at least one side of the surface of the modified base film; the modified base film adopts the modified base film of the first aspect of the present application or the modified base film prepared by the preparation method of the second aspect of the present application.

[0065] The fourth aspect of the present application provides an electrode, comprising the composite current collector of the third aspect of the present application and an active material layer and a transfer sheet located on at least one side surface of the composite current collector, wherein along the second direction, the length of the projection of the transfer sheet on the modified layer accounts for 60%-100% of the coating width of the conductive coating area, and the transfer sheet does not contact the active material layer.

[0066] In some embodiments, a distance between an edge of the adapter sheet adjacent to the adhesion-modified region and an edge of the conductive coating region adjacent to the adhesion-modified region is 0-12 mm.

[0067] The fifth aspect of the present application provides a battery cell, comprising the electrode of the fourth aspect of the present application.

[0068] The sixth aspect of the present application provides an electrical device, comprising the battery cell of the fifth aspect of the present application.

[0069] The modified base film provided above, the modified layer on the surface of the base film body includes an adhesion modified region and a conductive coating region. When it is used for a composite current collector, the adhesion modified region can improve the adhesion between the metal layer and the base film layer; the conductive coating region can enhance the conductivity of the base film layer, thereby improving the conductive properties of the composite current collector, and further improving the charge and discharge rate of the battery cell using the composite current collector, and improving the fast charging performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0071] Figure 1 A schematic diagram of the structure of a base film body with a modified layer provided in one embodiment.

[0072] Figure 2 A process flow chart for preparing a modified layer on the surface of a base film body is provided in accordance with one embodiment.

[0073] Figure 3 A schematic diagram of an electrode structure provided in one embodiment.

[0074] Figure 4 This is a structural diagram of the modified layer in the modified base film prepared in Example 1.

[0075] Figure 5 These are the test results of the composite current collector copper foil electrolyte immersion in Example 1 and Comparative Example 1.

[0076] Figure 6 These are the test results of the roll welding performance of the composite current collector copper foil in Example 1 and Comparative Example 2.

[0077] Figure 7 It is a comparison chart of 1C charge-discharge cycle performance of Example 1 and Comparative Examples 1-2.

[0078] Figure 8 It is a comparison chart of the 3C charge-discharge cycle performance of Example 1 and Comparative Examples 1-2.

[0079] Fig. 9 Schematic diagram of the test points of the internal resistance of the negative electrode sheet in Examples 1-7 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0080] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0081] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0082] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or".

[0083] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0084] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0085] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0086] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0087] In this application, unless otherwise specified, the size, particle size, and diameter generally refer to the average value. In this application, "particle size" and "particle size" have the same definition, both representing the average particle size of a sphere or a spheroid.

[0088] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0089] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0090] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0091] In the description of the application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0092] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0093] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0094] The PET material used in the middle polymer layer of the composite current collector contains an unstable group, an ester bond, in its molecules. Currently, the performance of PET copper foil has "dive" in the late stage of battery high-temperature cycle testing, and it cannot be used on a large scale in energy storage and power battery production. PP material has high chemical stability because it only has carbon-carbon bonds in its molecular chain. It does not react with most chemical reagents except strong oxidants. However, the polarity of PP molecules is very weak and it has strong hydrophobicity, which results in weak bonding between the metal layer and the base film layer during coating.

[0095] In order to solve the problem of weak bonding between PP materials and metal coatings, currently hard PP substrates are usually sprayed with PP treatment agents or treated chemically to improve the wetting tension of the substrate, thereby improving the bonding strength of the coating. However, due to the relatively soft material and ultra-thin thickness of the composite current collector PP base film, the above method is not applicable. Methods to improve the adhesion of the composite current collector PP base film need to be further developed.

[0096] In addition, due to the presence of insulating polymer film in the composite current collector, there are many problems with the existing spot welding and butterfly welding processes for welding the tabs. It is difficult to weld in place with conventional power of existing spot welding and butterfly welding. Increasing the welding power makes it difficult to control over-welding. Over-welding will cause the battery cell to self-discharge, resulting in battery cell cycle failure and failure to meet large-scale mass production needs. In response to the above-mentioned welding difficulties, the solution currently discussed in the industry is to roll weld pure metal on both sides of the PP film, and then cut it to leave the pure metal tabs for spot welding. However, there is still a probability that the pure metal and the polymer layer of the composite foil are not welded tightly during roll welding, and the roll welding results are greatly related to the substrate. In addition, the current situation of small contact area between conventional metal foil and composite current collector during roll welding and thin coating thickness of composite current collector will cause the composite current collector product to have low charge and discharge rate at the battery cell end, making it difficult to apply to fast charging application scenarios.

[0097] The present application performs zoned modification on the polypropylene base film body, and a modified adhesive slurry is coated on a partial area on the surface of the polypropylene base film body to prepare an adhesion modified area, thereby improving the adhesion of the base film body, thereby improving the adhesion of the metal layer; a conductive coating is coated on the remaining area on the surface of the polypropylene base film body to prepare a conductive coating area, thereby improving the conductive performance of the base film body and improving the fast charging performance of the battery cell using the composite current collector.

[0098] One or more embodiments of the present application provide a modified base film, comprising a base film body and a modified layer located on at least one side surface of the base film body; the modified layer comprises an adhesion modification region and a conductive coating region, the coating width of the adhesion modification region along the first direction is the same as the coating width of the conductive coating region along the first direction, the coating width of the conductive coating region along the second direction is 1.5cm-2.5cm, and the first direction and the second direction are respectively parallel to two adjacent edges of the base film body; when the modified base film is used in an electrode, the projection of the active material layer on the modified layer is located in the adhesion modification region, and the projection of the adapter sheet on the modified layer is located in the conductive coating region.

[0099] As an example, the coating width of the conductive coating region along the second direction may be, but is not limited to, 1.5 cm, 1.6 cm, 1.7 cm, 1.8 cm, 1.9 cm, 2 cm, 2.1 cm, 2.2 cm, 2.3 cm, 2.4 cm, 2.5 cm, or a range between any two of the above lengths, etc. When the coating width of the conductive coating region along the second direction is within the above range, it is beneficial to ensure the conductive performance while avoiding a smaller active material layer due to a smaller adhesion modified region, thereby reducing the energy density of the battery cell.

[0100] It can be understood that the modified layer on the surface of the base film body in the modified base film includes an adhesion modified region and a conductive coating region. When it is used for a composite current collector, the adhesion modified region can enhance the adhesion between the metal layer and the base film layer; the conductive coating region can enhance the conductivity of the base film layer, thereby improving the conductive properties of the composite current collector, and further improving the charge and discharge rate of the battery cell using the composite current collector, and improving the fast charging performance of the battery cell.

[0101] Figure 1 A schematic diagram of the structure of a modified base film provided in one embodiment; Figure 1 As shown, the modified layer includes an adhesion modified region and a conductive coating region.

[0102] In some embodiments, two adjacent edges of the adhesion modified region and the conductive coating region are connected by a connector, and the material of the connector includes at least one of aluminum oxide, titanium dioxide, silicon dioxide and zinc oxide. Thus, the connector has a certain bonding force with both the adhesion modified region and the conductive coating region, and the modified layer is formed into a whole by the connector to avoid the surface of the base film from splitting during the use of the battery.

[0103] In some embodiments, the adhesion modified region comprises one or more of a binder, a curing agent, a dispersant, a coupling agent, and a lubricant.

[0104] As a possible implementation manner, the mass ratio of the binder to the curing agent is (20-40):(3-7); for example, it can be but not limited to 40:7, 35:6, 30:5, 25:4, 20:3 or a range between any two of the above ratios.

[0105] In some exemplary embodiments, the mass ratio of the binder to the dispersant is (20-40):(3-7); for example, it can be but not limited to 20:7, 40:7, 35:6, 30:5, 25:4, 20:3, 40:3 or a range between any two of the above ratios.

[0106] In some optional embodiments, the mass ratio of the binder to the coupling agent is (20-40):(1-5); for example, it can be but not limited to 20:5, 40:5, 35:4, 30:3, 25:2, 20:1, 40:1 or a range between any two of the above ratios.

[0107] In some embodiments, the mass ratio of the binder to the lubricant is (20-40):(1-5); for example, it can be but not limited to 20:5, 40:5, 35:4, 30:3, 25:2, 20:1, 40:1 or a range between any two of the above ratios.

[0108] In some embodiments, the binder includes one or more of polymethyl methacrylate, carboxymethyl cellulose, modified epoxy resin, polyethylene-polypropylene copolymer, and polyurethane.

[0109] As a possible implementation, the curing agent includes one or more of N,N-dimethylformamide, polyamide, dicyandiamide and maleic anhydride.

[0110] In some optional embodiments, the dispersant includes one or more of hydroxypropyl methylcellulose, glycidyl butyl ether, polycarboxylic acid amine and polyamine polyamide salt.

[0111] In some embodiments, the coupling agent includes one or more of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane and vinyltriethoxysilane.

[0112] As a possible implementation, the lubricant includes one or more of silicone oil, alkyd resin, polyvinyl alcohol and silicate.

[0113] In some embodiments, the conductive coating region comprises one or more of a base resin, a conductive filler, and an additive.

[0114] In some optional embodiments, the mass ratio of the base resin and the conductive filler is (20-85):(2-70); for example, it can be but is not limited to 20:70, 30:70, 40:70, 50:70, 60:70, 70:70, 80:70, 85:70, 20:10, 30:10, 40:10, 50:10, 60:10, 70:10, 80:10, 85:10, 45:5, 20:2, 30:2, 40:2, 50:2, 60:2, 70:2, 80:2, 85:2 or a range between any two of the above mass ratios, etc.

[0115] As a possible implementation manner, the mass ratio of the base resin and the additive is (20-85):(1.5-3.5); for example, it can be but not limited to 20:3.5, 30:3.5, 40:3.5, 50:3.5, 60:3.5, 70:3.5, 80:3.5, 85:3.5, 40:1.5, 50:1.5, 60:1.5, 70:1.5, 80:1.5, 85:1.5 or a range between any two of the above ratios.

[0116] As a possible implementation manner, the base resin includes one or more of thermoplastic acrylic resin, polyurethane resin, epoxy resin, polystyrene butadiene resin, silicone resin, alkyd resin and modified resins corresponding to the above resins.

[0117] In some optional embodiments, the auxiliary agent includes one or more of an initiator, a wetting agent, a defoaming agent, and a coupling agent.

[0118] In some exemplary embodiments, the conductive filler includes one or more mixtures of metal-based conductive fillers, carbon-based conductive fillers, non-metal-based conductive fillers, and conductive polymer fillers.

[0119] In some optional embodiments, the metal-based conductive filler includes one or more of Ag, Ni and Cu.

[0120] In some embodiments, the carbon-based conductive filler includes one or more of carbon black, graphite, graphene, carbon nanotubes and carbon fibers.

[0121] In some optional embodiments, the non-metallic conductive filler includes one or more of tin oxide, zinc oxide, antimony dioxide and titanium dioxide.

[0122] As a possible implementation, the conductive polymer filler includes one or more of polyaniline, polypyrrole, polythiophene, and poly(3,4-ethylenedioxythiophene) polystyrene sulfonate.

[0123] In some embodiments, the coating thickness of the modified layer along the third direction is 260nm-340nm, and the third direction is perpendicular to the first direction and the second direction, respectively. As an example, the coating width of the modified layer along the third direction can be, but is not limited to, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 320nm, 330nm, 340nm or a range between any two of the above thicknesses. When the coating thickness of the modified layer is within the above range, it is beneficial to improve the conductive performance of the modified layer.

[0124] As a possible implementation, the material of the base film body includes polypropylene.

[0125] One or more embodiments of the present application provide a method for preparing a modified base film, which can be used to prepare the above-mentioned modified base film. The preparation method includes the following steps: coating a modified adhesive slurry on a partial area of ​​at least one side of the surface of the base film body, and coating a conductive coating on a partial area to prepare a bonding modified area and a conductive coating area respectively, to form a modified layer; drying the base film body after forming the modified layer; wherein the coating width of the bonding modified area along the first direction is the same as the coating width of the conductive coating area along the first direction, and the coating width of the conductive coating area along the second direction is 1.5cm-2.5cm, and the first direction and the second direction are respectively parallel to the two edges adjacent to the base film body; when the modified base film is used in an electrode, the projection of the active material layer on the modified layer is located in the bonding modified area, and the projection of the adapter on the modified layer is located in the conductive coating area.

[0126] When preparing the modified base film, the modified adhesive slurry and the conductive coating are coated on at least one side of the surface of the base film body in a partitioned manner to modify the surface of the base film body and prepare an adhesion modified area and a conductive coating area, thereby improving the adhesion after coating and the conductive properties of the base film body.

[0127] It should be noted that the modified adhesive slurry and the conductive coating are coated on the surface of the base film body by micro-concave coating.

[0128] In some embodiments, before the step of drying the base film body after forming the modified layer, the method further includes: filling an adhesive material between two adjacent edges of the adhesion modified region and the conductive coating region.

[0129] In some optional embodiments, the bonding material includes one or more of aluminum oxide, titanium dioxide, silicon dioxide and zinc oxide.

[0130] In some embodiments, the modified binder slurry comprises a binder, a curing agent, a dispersant, a coupling agent, a lubricant, and a solvent A.

[0131] As a possible implementation, the mass proportion of the binder in the modified adhesive slurry is 20%-40%, for example, it can be but not limited to 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40% or the range between any two of the above mass proportions, etc. This is conducive to improving the bonding performance of the modified adhesive slurry.

[0132] In some optional embodiments, the mass proportion of the curing agent in the modified adhesive slurry is 3%-7%, for example, it can be but not limited to 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or the range between any two of the above mass proportions, etc. This is conducive to improving the cross-linking and curing performance of the modified adhesive slurry.

[0133] In some exemplary embodiments, the mass proportion of the dispersant in the modified binder slurry is 3%-7%, for example, but not limited to 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, or a range between any two of the above mass proportions, etc. This is conducive to improving the stability and dispersibility of the modified binder slurry and reducing the risk of binder agglomeration and aggregation.

[0134] In some optional embodiments, the mass proportion of the coupling agent in the modified adhesive slurry is 1%-5%, for example, but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range between any two of the above mass proportions, etc. This is beneficial to improving the bonding strength, heat resistance and chemical resistance of the modified adhesive slurry.

[0135] In some embodiments, the mass percentage of the lubricant in the modified adhesive slurry is 1%-5%, for example, but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range between any two of the above mass percentages, etc. This is beneficial to reduce the friction of the modified adhesive slurry and improve its fluidity.

[0136] As a possible implementation, solvent A includes ethylene glycol.

[0137] In some embodiments, the conductive coating comprises a base resin, a conductive filler, an additive and a solvent B.

[0138] As a possible implementation manner, the conductive coating comprises a base resin, a conductive filler, an additive and a solvent B.

[0139] In some optional embodiments, the mass percentage of the base resin in the conductive coating is 20%-85%, for example, but not limited to 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or a range between any two of the above mass percentages, etc. This is beneficial to improving the adhesion performance of the conductive coating area.

[0140] As a possible implementation, the mass proportion of the conductive filler in the conductive coating is 2%-70%, for example, but not limited to 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or the range between any two of the above mass proportions, etc. This is conducive to improving the conductive performance of the conductive coating area.

[0141] In some embodiments, the mass percentage of the additive in the conductive coating is 1.5%-3.5%, for example, but not limited to 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, or a range between any two of the above mass percentages, etc. This is beneficial to improving the curing performance, bonding performance, fluidity, heat resistance, chemical resistance and dispersibility of the conductive coating area.

[0142] In some embodiments, the auxiliary agent includes one or more of an initiator, a wetting agent, a defoaming agent, and a coupling agent.

[0143] As a possible implementation manner, the solvent B includes one or more of toluene, ethanol, acetone, xylene, cyclohexane, cyclohexanone, ethyl acetate, n-butanol, isopropanol, dimethylformamide and butyl acetate.

[0144] In some embodiments, before the step of preparing the modified layer, the preparation method further comprises: plasma cleaning the base film body, thereby facilitating the improvement of the initial wetting tension of the base film body.

[0145] In some embodiments, the cleaning gas for plasma cleaning includes argon.

[0146] In some embodiments, the power of plasma cleaning is 110W-180W; for example, it can be but is not limited to 110W, 120W, 130W, 140W, 150W, 160W, 170W, 180W or a range between any two of the above powers.

[0147] In some embodiments, the plasma cleaning time is 6s-10s; for example, it can be but not limited to 6s, 7s, 8s, 9s, 10s or a range between any two of the above times.

[0148] It should be noted that the power and time of plasma cleaning can be combined in any appropriate manner, and both can be selected from any power and time of plasma cleaning described in this document.

[0149] As a possible implementation manner, the bias voltage of the plasma cleaning is 400V.

[0150] In some embodiments, the gas flow rate for plasma cleaning is 400 sccm.

[0151] In some embodiments, the step of drying the base film body after the modified layer is formed includes: sequentially performing far-infrared radiation heating drying and oven drying on the base film body after the modified layer is formed.

[0152] In some optional embodiments, the infrared band used for far-infrared radiation heating drying is 3μm-14μm; for example, it can be but not limited to 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or the range between any two of the above infrared bands, etc.

[0153] In some embodiments, the maximum power density of far-infrared radiation heating and drying is 3W / cm 2 -5W / cm 2 ; For example, it can be but not limited to 3W / cm 2 、3.5W / cm 2 , 4W / cm 2 , 4.5W / cm 2 , 5W / cm 2 Or the range between any two of the above maximum power densities, etc.

[0154] As a possible implementation manner, the drying time of far-infrared radiation heating drying is 1 min-3 min; for example, it can be but not limited to 1 min, 1.5 min, 2 min, 2.5 min, 3 min or a range between any two of the above drying times.

[0155] It should be noted that the infrared band, maximum power density and drying time of far-infrared radiation heating drying can be combined in any appropriate way, and the three can be selected from any infrared band, maximum power density and drying time of far-infrared radiation heating drying described in this article.

[0156] As non-limiting examples, materials selected for far-infrared radiation heating and drying include carbon fiber or tungsten wire.

[0157] In some optional embodiments, the oven drying temperature is 60°C-100°C; for example, it can be but not limited to 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or a range between any two of the above temperatures.

[0158] In some exemplary embodiments, the oven drying time is 1 min-3 min; for example, it can be but not limited to 1 min, 1.5 min, 2 min, 2.5 min, 3 min or a range between any two of the above drying times, etc.

[0159] It should be noted that the temperature and time of oven drying can be combined in any suitable manner, and both can be selected from any oven drying temperature and time described in this document.

[0160] Figure 2 A process flow chart of a modified base film provided in one embodiment of the present application, such as Figure 2 As shown, when preparing the modified layer on the surface of the base film body, the base film body is first plasma cleaned, then subjected to partitioned adhesion modification coating and conductive coating, and finally the base film body is dried to complete the preparation of the modified layer.

[0161] One or more embodiments of the present application provide a composite current collector, comprising a modified base film and a metal layer located on at least one side of the surface of the modified base film; the modified base film comprises a base film body and a modified layer located on at least one side of the surface of the base film body, the modified layer comprises an adhesion modified region and a conductive coating region, the coating width of the adhesion modified region along the first direction is the same as the coating width of the conductive coating region along the first direction, the coating width of the conductive coating region along the second direction is 1.5cm-2.5cm, and the first direction and the second direction are respectively parallel to the two adjacent edges of the base film body; when the composite current collector is used in an electrode, the projection of the active material layer on the modified layer is located in the adhesion modified region, and the projection of the adapter on the modified layer is located in the conductive coating region.

[0162] In some embodiments, the modified base film in the composite current collector is the modified base film described above, and has the same technical features as the modified base film described above, which will not be described in detail herein.

[0163] As a non-limiting example, the preparation method of the composite current collector includes: forming a metal layer on the surface of the modified layer away from the base film body; the specific method includes:

[0164] Step S1, magnetron sputtering: Before starting sputtering, confirm the equipment status and cleanliness. If there is no abnormality, the film can be penetrated. Close the sputtering chamber and evacuate the vacuum for 8 hours. The film speed is 0.1 m / min and the vacuum degree needs to reach 7×10 -3 -1×10 -3 Kpa; sputtering is carried out after vacuuming, the winding and unwinding tension value is 70N, the line speed during sputtering is 5m / min, and the coating roller temperature is 0℃; after sputtering, the temperature and pressure are restored to obtain the semi-finished product and the hatch is opened.

[0165] Step S2, winding water electroplating: after sputtering, the semi-finished product is cut into pieces, the line speed is 110m / min, the winding tension is 60N, the unwinding tension is 50N, the width after cutting is 1220mm, and it is transferred to the water electroplating process; the electroplating line speed is 5m / min, the winding tension is 50N, and the unwinding tension is 60N; during the electroplating process, moderate stirring is performed to ensure uniform distribution of the solution, the concentration of copper sulfate is 100g / L, the concentration of brightener is 5ml / L, and the concentration of leveling agent is 1ml / L; the water-plated finished product after cleaning is subjected to antioxidant treatment to form a protective film on its surface; and it is dried to remove excess moisture and prevent oxidation.

[0166] One or more embodiments of the present application provide an electrode, comprising a composite current collector and an active material layer and a transfer sheet located on at least one side surface of the composite current collector; the composite current collector comprises a modified base film and a metal layer located on at least one side surface of the modified base film; the modified base film comprises a base film body and a modified layer located on at least one side surface of the base film body; the modified layer comprises an adhesion modification region and a conductive coating region, a projection of the active material layer on the modified layer is located in the adhesion modification region, and a projection of the transfer sheet on the modified layer is located in the conductive coating region; a coating width of the adhesion modification region along the first direction is the same as a coating width of the conductive coating region along the first direction, a coating width of the conductive coating region along the second direction is 1.5 cm-2.5 cm, and the first direction and the second direction are respectively parallel to two edges adjacent to the base film body; along the second direction, the length of the projection of the transfer sheet on the modified layer accounts for 60%-100% of the coating width of the conductive coating region, and the transfer sheet does not contact the active material layer.

[0167] As an example, along the second direction, the percentage of the projection length of the adapter sheet on the modified layer to the coating width of the conductive coating area can be, but is not limited to, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 100% or a range between any two of the above values. Since the bonding force between the base film conductive layer and the base film is weak, if the percentage of the projection length of the adapter sheet on the modified layer to the coating width of the conductive coating area is lower than the above range, the base film conductive coating that is not welded to the adapter sheet is easily separated from the base film body due to the pulling force of the roll welding equipment on the film surface during the roll welding process, and then the metal layer in the separated area is easily torn due to the pulling of the roll welding equipment on the film surface during the roll welding process, affecting the current transmission performance of the current collector, and ultimately resulting in a decrease in the rate performance of the battery. Therefore, when the percentage of the projection length of the adapter plate on the modified layer along the second direction to the coating width of the conductive coating area is within the above range, it is beneficial to increase the welding contact area of ​​the adapter plate and reduce the risk of tearing of the conductive layer due to pulling of the adapter plate during welding.

[0168] In some embodiments, the distance between the edge of the adapter sheet adjacent to the adhesion modification area and the edge of the conductive coating area adjacent to the adhesion modification area is 0-12 mm; for example, it can be but not limited to 0, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm or the range between any two of the above distances, etc. Since the adhesion between the conductive layer of the base film and the base film is relatively weak, if the distance between the edge of the adapter sheet adjacent to the adhesion modification area and the edge of the conductive coating area adjacent to the adhesion modification area is greater than 12 mm, the conductive coating of the base film that is not welded to the adapter sheet is easily separated from the base film body due to the pulling force of the roll welding equipment on the film surface during the roll welding process, and then the metal layer in the separation area is easily torn due to the pulling of the roll welding equipment on the film surface during the roll welding process, affecting the current transmission performance of the current collector, and ultimately resulting in a decrease in the rate performance of the battery.

[0169] In some embodiments, the modified base membrane in the electrode is the modified base membrane described above, and has the same technical features as the modified base membrane described above, which will not be described in detail here.

[0170] Figure 3 A schematic diagram of an electrode structure provided in one embodiment, comprising Figure 3It can be seen that the electrode includes a composite current collector, an active material layer 41 and a transfer sheet 42. The composite current collector includes a base film body 1, a modified layer located on the surface of the base film body 1, and a metal layer 3 located on the surface of the modified layer away from the base film body 1. The modified layer includes an adhesion modified region 21 and a conductive coating region 22. The projection of the active material layer 41 on the modified layer is located in the adhesion modified region 21, and the projection of the transfer sheet 42 on the modified layer is located in the conductive coating region 22. The distance between the edge of the transfer sheet adjacent to the adhesion modified region and the edge of the conductive coating region adjacent to the adhesion modified region is as shown in FIG. Figure 3 The area shown in the figure is denoted as a, 0≤a≤12mm.

[0171] One or more embodiments of the present application provide a battery cell including the above-mentioned electrode.

[0172] The battery cell includes the composite current collector and has excellent fast charging performance.

[0173] One or more embodiments of the present application provide an electrical device including the above-mentioned battery cell.

[0174] The electric device of the present application includes the battery cell provided by the present application, and thus has at least the same advantages as the battery cell.

[0175] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following embodiments are preferably referred to the guidance given in the present invention, and can also be carried out according to the experimental manual or conventional conditions in the art, or according to the conditions recommended by the manufacturer, or with reference to experimental methods known in the art.

[0176] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0177] 1. Preparation of modified polypropylene base film

[0178] Example 1

[0179] Step S1, plasma cleaning: place the rolled polypropylene base film body into a winding cold source plasma cleaning machine (reaction area length is 500mm), the cleaning gas is argon, the plasma cleaning power is set to 150W, the bias is 400V, the gas flow rate is 400sccm, and the cleaning time is 10s to increase the initial wetting tension of the base film.

[0180] Step S2, preparation of modified adhesion region: prepare modified adhesive slurry, the adhesive slurry contains polymethyl methacrylate (binder), N,N-dimethylformamide (curing agent), hydroxypropyl methylcellulose (dispersant), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (coupling agent) and silicone oil (lubricant), with the mass proportions of 30%, 5%, 5%, 3% and 3%, respectively, and the remaining components are all solvent ethylene glycol; all the above substances are stirred using a high-speed homogenizer at a speed of 3000r / min for 1.5h to prepare modified adhesive slurry, place the obtained modified adhesive slurry in a vacuum oven for 2h for defoaming treatment, and then evenly coat the slurry on both sides of the base film body where the adhesion needs to be improved by micro-concave coating, with a thickness of 300nm, and obtain the adhesion modified region after low-temperature drying.

[0181] Step S3, preparation of conductive coating area: at the reserved pole ear welding place, a conductive coating is applied on the surface of the polypropylene base film body, the base resin in the conductive coating is a polyurethane resin, accounting for 25% by mass; the conductive filler is Ag, accounting for 70% by mass; the auxiliary agent is aminopropyl triethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene; the viscosity of the conductive coating is 18000cps, the width of the coating parallel to the collector direction on the reserved pole ear welding foil is 2cm, and the coating thickness perpendicular to the collector direction is 300nm, which is consistent with the thickness of the adhesion modified area, and then dried at 60°C for 12h to form a conductive coating area, and then connected with an aluminum oxide solution at the edge in contact with the adhesive, and the thickness of both sides reaches 300nm.

[0182] Step S4, drying: the base film body after the partition coating is completed is dried by a far-infrared radiation heating system and an oven in sequence, the infrared band is selected to be 5-7μm, the material is carbon fiber, and the maximum power density is 4W / cm 2 , infrared drying time is 2 minutes, oven drying temperature is 80°C, oven drying time is 2 minutes, and finally a partition coating modified polypropylene base film is obtained.

[0183] The modified layer structure in the modified base film prepared in Example 1 is as follows: Figure 4 shown.

[0184] Example 2

[0185] Step S1, plasma cleaning: place the rolled polypropylene base film body into a winding cold source plasma cleaning machine (reaction area length is 500mm), the cleaning gas is argon, the plasma cleaning power is set to 130W, the bias is 400V, the gas flow rate is 400sccm, and the cleaning time is 8s to increase the initial wetting tension of the base film.

[0186] Step S2, preparation of modified adhesion region: prepare modified adhesive slurry, the adhesive slurry contains polymethyl methacrylate (binder), N,N-dimethylformamide (curing agent), hydroxypropyl methylcellulose (dispersant), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (coupling agent) and silicone oil (lubricant), with the mass proportions of 25%, 4%, 4%, 2% and 2%, respectively, and the remaining components are all solvent ethylene glycol; all the above substances are stirred using a high-speed homogenizer at a speed of 4000r / min for 1h to prepare modified adhesive slurry, the obtained modified adhesive slurry is placed in a vacuum oven for 2h for defoaming treatment, and then the slurry is evenly coated on both sides of the base film body where the adhesion needs to be improved by micro-concave coating, with a thickness of 280nm, and the adhesion modified region is obtained after low-temperature drying.

[0187] Step S3, preparation of conductive coating area: at the reserved pole ear welding place, a conductive coating is applied on the surface of the polypropylene base film body, the base resin in the conductive coating is a polyurethane resin, accounting for 25% by mass; the conductive filler is Ag, accounting for 70% by mass; the auxiliary agent is aminopropyl triethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene; the viscosity of the conductive coating is 17000cps, the width of the coating parallel to the collector direction on the reserved pole ear welding foil is 2cm, and the coating thickness perpendicular to the collector direction is 280nm, which is consistent with the thickness of the adhesion modified area, and then dried at 60°C for 12h to form a conductive coating area, and then connected with the edge in contact with the adhesive using an aluminum oxide solution, and the thickness of both sides reaches 280nm.

[0188] Step S4, drying: the base film body after the partition coating is completed is dried by a far-infrared radiation heating system and an oven in sequence, the infrared band is selected to be 3-4μm, the material is tungsten wire, and the maximum power density is 3W / cm 2 , infrared drying time is 1.5 min, oven drying temperature is 70 ° C, oven drying time is 1.5 min, and finally a partition coating modified polypropylene base film is obtained.

[0189] Example 3

[0190] Step S1, plasma cleaning: place the rolled polypropylene base film body into a winding cold source plasma cleaning machine (reaction area length is 500 mm), the cleaning gas is argon, the plasma cleaning power is set to 110 W, the bias voltage is 400 V, the gas flow rate is 400 sccm, and the cleaning time is 6 s to increase the initial wetting tension of the base film.

[0191] Step S2, preparation of modified adhesion region: prepare modified adhesive slurry, the adhesive slurry contains polymethyl methacrylate (binder), N,N-dimethylformamide (curing agent), hydroxypropyl methylcellulose (dispersant), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (coupling agent) and silicone oil (lubricant), with the mass proportions of 20%, 3%, 3%, 1% and 1%, respectively, and the remaining components are all solvent ethylene glycol; all the above substances are stirred using a high-speed homogenizer at a speed of 3000r / min for 2h to prepare modified adhesive slurry, the obtained modified adhesive slurry is placed in a vacuum oven for 2h for defoaming treatment, and then the slurry is evenly coated on both sides of the base film body where the adhesion needs to be improved by micro-concave coating, with a thickness of 260nm, and the adhesion modified region is obtained after low-temperature drying.

[0192] Step S3, preparation of conductive coating area: at the reserved pole ear welding place, a conductive coating is applied on the surface of the polypropylene base film body, wherein the base resin in the conductive coating is a polyurethane resin, accounting for 25% by mass; the conductive filler is Ag, accounting for 70% by mass; the auxiliary agent is aminopropyl triethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene; the viscosity of the conductive coating is 16000cps, and the width of the coating parallel to the collector direction on the reserved pole ear welding foil is 2cm, and the coating thickness perpendicular to the collector direction is 260nm, which is consistent with the thickness of the adhesion modified area, and then dried at 60°C for 12h to form a conductive coating area, and then connected with the edge in contact with the adhesive using an aluminum oxide solution, and the thickness of both sides reaches 260nm.

[0193] Step S4, drying: the base film body after the partition coating is completed is dried by a far-infrared radiation heating system and an oven in sequence, the infrared band is selected to be 5-7μm, the material is carbon fiber, and the maximum power density is 3W / cm 2 , infrared drying time is 1.0 min, oven drying temperature is 60°C, oven drying time is 1.0 min, and finally a partition coating modified polypropylene base film is obtained.

[0194] Example 4

[0195] Step S1, plasma cleaning: place the rolled polypropylene base film body into a winding cold source plasma cleaning machine (reaction area length is 500 mm), the cleaning gas is argon, the plasma cleaning power is set to 160 W, the bias is 400 V, the gas flow rate is 400 sccm, and the cleaning time is 12 s to increase the initial wetting tension of the base film.

[0196] Step S2, preparation of modified adhesion region: prepare modified adhesive slurry, the adhesive slurry contains polymethyl methacrylate (binder), N,N-dimethylformamide (curing agent), hydroxypropyl methylcellulose (dispersant), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (coupling agent) and silicone oil (lubricant), with the mass proportions of 35%, 6%, 6%, 4% and 4%, respectively, and the remaining components are all solvent ethylene glycol; all the above substances are stirred using a high-speed homogenizer at a speed of 3000r / min for 2h to prepare modified adhesive slurry, the obtained modified adhesive slurry is placed in a vacuum oven for 2h for defoaming treatment, and then the slurry is evenly coated on both sides of the base film body where the adhesion needs to be improved by micro-concave coating, with a thickness of 320nm, and the adhesion modified region is obtained after low-temperature drying.

[0197] Step S3, preparation of conductive coating area: at the reserved pole ear welding place, a conductive coating is applied on the surface of the polypropylene base film body, wherein the base resin in the conductive coating is a polyurethane resin, accounting for 25% by mass; the conductive filler is Ag, accounting for 70% by mass; the auxiliary agent is aminopropyl triethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene; the viscosity of the conductive coating is 19000cps, and the width of the coating parallel to the collector direction on the reserved pole ear welding foil is 2cm, and the coating thickness perpendicular to the collector direction is 320nm, which is consistent with the thickness of the adhesion modified area, and then dried at 60°C for 12h to form a conductive coating area, and then connected with the edge in contact with the adhesive using an aluminum oxide solution, and the thickness of both sides reaches 320nm.

[0198] Step S4, drying: the base film body after the partition coating is completed is dried by a far-infrared radiation heating system and an oven in sequence, the infrared band is selected to be 8-12μm, the material is carbon fiber, and the maximum power density is 5W / cm 2 , infrared drying time is 2.5min, oven drying temperature is 90℃, oven drying time is 2.5min, and finally a partition coating modified polypropylene base film is obtained.

[0199] Example 5

[0200] Step S1, plasma cleaning: place the rolled polypropylene base film body into a winding cold source plasma cleaning machine (reaction area length is 500 mm), the cleaning gas is argon, the plasma cleaning power is set to 180 W, the bias is 400 V, the gas flow rate is 400 sccm, and the cleaning time is 14 s to increase the initial wetting tension of the base film.

[0201] Step S2, preparation of modified adhesion region: prepare modified adhesive slurry, the adhesive slurry contains polymethyl methacrylate (binder), N,N-dimethylformamide (curing agent), hydroxypropyl methylcellulose (dispersant), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (coupling agent) and silicone oil (lubricant), with the mass proportions of 40%, 7%, 7%, 5% and 5%, respectively, and the remaining components are all solvent ethylene glycol; all the above substances are stirred using a high-speed homogenizer at a speed of 3000r / min for 2h to prepare modified adhesive slurry, the obtained modified adhesive slurry is placed in a vacuum oven for 2h for defoaming treatment, and then the slurry is evenly coated on both sides of the base film body where the adhesion needs to be improved by micro-concave coating, with a thickness of 340nm, and the adhesion modified region is obtained after low-temperature drying.

[0202] Step S3, preparation of conductive coating area: at the reserved pole ear welding place, a conductive coating is applied on the surface of the polypropylene base film body, the base resin in the conductive coating is a polyurethane resin, accounting for 25% by mass; the conductive filler is Ag, accounting for 70% by mass; the auxiliary agent is aminopropyl triethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene; the viscosity of the conductive coating is 20000cps, the width of the coating parallel to the collector direction on the reserved pole ear welding foil is 2cm, and the coating thickness perpendicular to the collector direction is 340nm, which is consistent with the thickness of the adhesion modified area, and then dried at 60℃ for 12h to form a conductive coating area, and then connected with the edge in contact with the adhesive using an aluminum oxide solution, and the thickness of both sides reaches 340nm.

[0203] Step S4, drying: the base film body after the partition coating is completed is dried by a far-infrared radiation heating system and an oven in sequence, the infrared band is selected to be 10-14μm, the material is tungsten wire, and the maximum power density is 5W / cm 2 , infrared drying time is 3.0 min, oven drying temperature is 100°C, oven drying time is 3.0 min, and finally a partition coating modified polypropylene base film is obtained.

[0204] Example 6

[0205] The preparation methods of Example 6 are similar to those of Example 1, except that the width of the coating on the reserved tab welding foil parallel to the current collector direction in step S3 of Example 6 is 1.5 cm, and the rest are the same.

[0206] Example 7

[0207] The preparation methods of Example 7 are similar to those of Example 1, except that the width of the coating parallel to the current collector direction on the reserved tab welding foil in step S3 of Example 7 is 2.5 cm, and the other methods are the same.

[0208] Example 8

[0209] The preparation methods of Example 8 are similar to those of Example 1, except that: in step S3 of Example 8, the base resin in the conductive coating is a polyurethane resin, accounting for 85% by mass; the conductive filler is carbon black, accounting for 10% by mass; the auxiliary agent is aminopropyltriethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene.

[0210] Example 9

[0211] The preparation methods of Example 9 are similar to those of Example 1, except that in step S3 of Example 9, the base resin in the conductive coating is a polyurethane resin, accounting for 75% by mass, the conductive filler is polyaniline, accounting for 20% by mass, the auxiliary agent is aminopropyltriethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene.

[0212] Example 10

[0213] A modified base film is prepared according to the preparation method of Example 1, and the modified base film is prepared into a composite current collector. The preparation method of the composite current collector is as follows:

[0214] Step 1, magnetron sputtering: Before starting sputtering, confirm the equipment status and cleanliness. If there is no abnormality, the film can be penetrated. Close the sputtering chamber and evacuate the vacuum for 8 hours. The film speed is 0.1m / min and the vacuum degree needs to reach 7×10 -3 -1×10 - 3 Kpa; sputtering is carried out after vacuuming, the winding and unwinding tension value is 70N, the line speed during sputtering is 5m / min, and the coating roller temperature is 0℃; after sputtering, the temperature and pressure are restored to obtain the semi-finished product and the hatch is opened.

[0215] Step 2, winding water electroplating: after sputtering, the semi-finished product is cut into pieces, the line speed is 110m / min, the winding tension is 60N, the unwinding tension is 50N, the width after cutting is 1220mm, and it is transferred to the water electroplating process; the electroplating line speed is 5m / min, the winding tension is 50N, and the unwinding tension is 60N; during the electroplating process, moderate stirring is performed to ensure that the solution is evenly distributed, the copper sulfate concentration is 100g / L, the brightener concentration is 5ml / L, and the leveling agent concentration is 1ml / L; the water-plated finished product after cleaning is subjected to antioxidant treatment to form a protective film on its surface; it is dried to remove excess moisture and prevent oxidation.

[0216] Step 3: Roll-weld pure metal copper foil on both sides of the composite current collector conductive area using a roll welding machine at a pressure of 4 KPa and an amplitude of 24%, so that the projected length of the metal copper foil on the modified layer accounts for 60% of the coating width of the conductive coating area.

[0217] Embodiment 11

[0218] The preparation methods of Example 11 are similar to those of Example 10, except that in step S3 of Example 11, the length of the projection of the metal copper foil on the modified layer accounts for 100% of the coating width of the conductive coating area.

[0219] Comparative Example 1

[0220] The polypropylene base film was not treated in any way and was directly used to prepare the composite current collector.

[0221] Comparative Example 2

[0222] The preparation method of Comparative Example 2 is similar to that of Example 1, except that only the adhesion of the polypropylene base film is modified, and the conductivity of the partitioned conductive coating is not enhanced. Others are the same. The preparation method of Comparative Example 2 is as follows:

[0223] Step S1 is the same as step S1 in Example 1.

[0224] Step S2, preparation of modified adhesion region: prepare modified adhesive slurry, the adhesive slurry contains polymethyl methacrylate (binder), N,N-dimethylformamide (curing agent), hydroxypropyl methylcellulose (dispersant), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (coupling agent) and silicone oil (lubricant), with the mass proportions of 30%, 5%, 5%, 3% and 3%, respectively, and the remaining components are all solvent ethylene glycol; all the above substances are stirred using a high-speed homogenizer at a speed of 3000r / min for 1.5h to prepare modified adhesive slurry, place the obtained modified adhesive slurry in a vacuum oven for 2h for defoaming treatment, and then evenly coat the slurry on both sides of the base film body where the adhesion needs to be improved by micro-concave coating, with a thickness of 300nm, and obtain the adhesion modified region after low-temperature drying.

[0225] Step S3 is the same as step S4 in Example 1.

[0226] Comparative Example 3

[0227] The preparation method of Comparative Example 3 is similar to that of Example 1, except that only the conductive coating is modified on the polypropylene base film body, and no partition adhesion enhancement modification is performed, and the other aspects are the same. The preparation method of Comparative Example 3 is as follows:

[0228] Step S1 is the same as step S1 in Example 1.

[0229] Step S2, preparation of conductive coating area: at the reserved pole ear welding, a conductive coating is applied on the surface of the polypropylene base film body, wherein the base resin in the conductive coating is a polyurethane resin, accounting for 30% by mass; the conductive filler is Ag, accounting for 70% by mass, and the auxiliary agent is aminopropyltriethoxysilane (coupling agent), accounting for 2% by mass, and the rest is toluene. The viscosity of the conductive coating is 18000cps, and the width of the coating parallel to the collector direction on the reserved pole ear welding foil is 2cm, and the coating thickness perpendicular to the collector direction is 300nm, and then dried at 60°C for 12h to form a conductive coating area.

[0230] Step S3 is the same as step S4 in Example 1.

[0231] Comparative Example 4

[0232] The preparation methods of Comparative Example 4 and Example 10 are similar, except that in step 3 of Comparative Example 4, the length of the projection of the metal copper foil on the modified layer accounts for 50% of the coating width of the conductive coating area.

[0233] 2. Performance Test

[0234] 1. Use Arcotest corona test pen (dyne value) to test the wetting tension (dyne value) of the adhesion modified area in Examples 1-9 and Comparative Examples 1-3. The test method is: draw a straight line on the surface of the base film. If the line is evenly distributed and does not have any beads, it means that the index marked on the dyne pen is lower than the dyne on the surface of the film, and a dyne pen with a higher reading needs to be replaced; if the line shrinks slowly, it means that the index marked on the dyne pen is higher than the dyne on the surface of the film, and a dyne pen with a lower reading needs to be replaced for measurement until the test result becomes spherical within 2S, indicating that the value of the test pen is the surface tension of the test material. The test results are shown in Table 1.

[0235] Table 1

[0236] Group Base film dyne value (mN / m) Example 1 50 Example 2 44 Example 3 42 Example 4 46 Example 5 48 Example 6 50 Example 7 50 Example 8 50 Example 9 50 Comparative Example 1 32 Comparative Example 2 50 Comparative Example 3 32

[0237] From the results of Examples 1-9 and Comparative Examples 1 and 3 in Table 1-2, it can be seen that the modified layer on the surface of the modified base film of the present application makes the surface tension of the modified base film greater.

[0238] 2. The base films in Example 1 and Comparative Example 1 were prepared into composite current collectors, and copper foil electrolyte immersion tests were performed.

[0239] The preparation method of the composite current collector is as follows:

[0240] Step S1, magnetron sputtering: Before starting sputtering, confirm the equipment status and cleanliness. If there is no abnormality, the film can be penetrated. Close the sputtering chamber and evacuate the vacuum for 8 hours. The film speed is 0.1 m / min and the vacuum degree needs to reach 7×10-3 -1×10 -3 Kpa; sputtering is carried out after vacuuming, the winding and unwinding tension value is 70N, the line speed during sputtering is 5m / min, and the coating roller temperature is 0℃; after sputtering, the temperature and pressure are restored to obtain the semi-finished product and the hatch is opened.

[0241] Step S2, winding water electroplating: after sputtering, the semi-finished product is cut into pieces, the line speed is 110m / min, the winding tension is 60N, the unwinding tension is 50N, the width after cutting is 1220mm, and it is transferred to the water electroplating process; the electroplating line speed is 5m / min, the winding tension is 50N, and the unwinding tension is 60N; during the electroplating process, moderate stirring is performed to ensure uniform distribution of the solution, the concentration of copper sulfate is 100g / L, the concentration of brightener is 5ml / L, and the concentration of leveling agent is 1ml / L; the water-plated finished product after cleaning is subjected to antioxidant treatment to form a protective film on its surface; it is dried to remove excess moisture and prevent oxidation; and the physical properties are tested after standing for 24 hours.

[0242] Test method: TC-E8633S high temperature electrolyte was selected to conduct the composite current collector copper foil electrolyte compatibility test immersion experiment, and 3cm×3cm composite current collector samples prepared in Example 1 and Comparative Example 1 were cut respectively (make sure there are no burrs on the cutting edge, and avoid the conductivity enhancement area when cutting in Example 1) and placed in a sealed can, and 10mL of the above electrolyte was added to seal it, and then placed in an oven at a high temperature of 85℃, and the coating shedding was checked at 12H, 48H, and 72H. The results are as follows Figure 5 shown.

[0243] Figure 5 Figure a is the test result after the composite current collector in Example 1 was immersed for 12 hours. It can be seen from the figure that the metal coating has no corrosion; Figure 5 b is the test result of the composite current collector in Example 1 after immersion for 48 hours. It can be seen from the figure that the edge of the metal coating is slightly corroded; Figure 5 Figure c is the test result of the composite current collector in Example 1 after immersion for 72 hours. It can be seen from the figure that the metal coating is corroded by 15%. Figure 5 Figure d is the test result of the composite current collector in Comparative Example 1 after immersion for 12 hours. It can be seen from the figure that the metal coating has no corrosion; Figure 5 Figure e is the test result of the composite current collector in comparative example 1 after immersion for 48 hours. It can be seen from the figure that the edge of the metal coating is slightly corroded; Figure 5 Figure c is the test result of the composite current collector in comparative example 1 after immersion for 72 hours. It can be seen from the figure that the metal coating is corroded by 15%.

[0244] Depend on Figure 5 It can be seen from the results that the setting of the modified layer in the present application does not deteriorate the corrosion resistance of the copper foil in the composite current collector. After immersion in the electrolyte for 72 hours, the corrosion resistance of the composite current collector copper foil in Example 1 and Comparative Example 1 is basically the same.

[0245] 3. The base films in Examples 1-9 and Comparative Examples 1-3 were prepared into composite current collectors, and the copper foil peeling force test was performed.

[0246] The preparation method of the composite current collector is the same as the preparation method of the composite current collector in 2 above.

[0247] A vertical tensile test machine was used to perform a coating pull-off test on the composite current collector copper foil to evaluate the peeling strength and coating bonding strength of the composite current collector copper foil and the composite current collector copper foil after immersion in an 85°C electrolyte for 12 hours. The electrolyte immersion method was the same as the electrolyte immersion method in 2. The copper foil peeling force test method is as follows:

[0248] The 3M double-sided tape (length 150mm, width 20mm) and the composite current collector copper foil sample (length 160mm, width 30mm) were sequentially pasted on the stainless steel plate, and a 1kg pressure roller was used to roll the surface of the 3M9080 single-sided tape at a uniform speed for 3 times in the same direction to ensure that the composite current collector copper foil sample and the 3M double-sided tape on the stainless steel plate were fully adhered. After that, 3M9080 single-sided tape (length 60mm, width 20mm) was adhered to the surface of the finished copper foil, and the 3M9080 single-sided tape port was connected to a white paper strip (length 150mm, width 20mm) at 5mm to fix it with the fixture. The stainless steel plate was fixed horizontally on the tensile machine fixture, and the peeling sample parameters (specimen length, width, etc.) were set, and a 180° coating pull-off test was performed at a speed of 500mm / min. The test results are shown in Table 2.

[0249] Table 2

[0250]

[0251] From the results of Examples 1-9 and Comparative Examples 1 and 3 in Table 1-2, it can be seen that the composite current collector copper foil prepared based on the modified base film of the present application has a greater peel strength and can still retain about 50% of the peel strength after being immersed in the electrolyte.

[0252] 4. The base films in Example 1 and Comparative Example 2 were prepared into composite current collectors, and the copper foil roll welding performance was tested.

[0253] The preparation method of the composite current collector is the same as the preparation method of the composite current collector in 2 above.

[0254] Test method: Roll weld the pure metal copper foil on both sides of the conductive area using a roll welder at a pressure of 4KPa and an amplitude of 24%. The distance between the end point of the roll weld and the end point of the conductive enhancement area (i.e., the distance between the edge of the roll weld adjacent to the adhesion modification area and the edge of the conductive coating area adjacent to the adhesion modification area) is controlled within the range of 0-12mm. After the roll weld is completed, manually tear and peel off the connection welds between the pure metal copper foil and the composite current collector. The residual rate of the pure metal copper foil embedded in the composite current collector after manual tearing and peeling is determined (at least 50% of the pure metal copper foil remaining at a single weld point is considered to be OK, and the peeled surface is the welding surface of the roll weld head) to determine whether the welding is firm. The schematic diagram of the peeling situation after roll welding is shown in the figure below. Figure 6 shown.

[0255] Figure 6 Figure a shows the peeling after roll welding of Example 1, and Figure b shows the peeling after roll welding of Comparative Example 2. Figure 6 It can be seen that after manually tearing off the connection welding points of the pure metal copper foil and the composite current collector, the residual rate of the pure metal copper foil in Example 1 and Comparative Example 2 is basically the same, indicating that the conductive coating in the present application enhances the conductivity of the composite current collector copper foil and does not affect the firmness of the roll welding.

[0256] 5. Lithium battery cell assembly and cell rate cycle charge and discharge test.

[0257] The rolled composite current collector copper foil and rolled aluminum foil prepared in the above embodiments and comparative examples were coated with slurry prepared according to a fixed material formula using a Kejing Zhida EI-300 coating machine. The material formula of the positive electrode plate is 95% by weight of lithium iron phosphate, 3% by weight of PVDF, and 2% by weight of SP; the material formula of the negative electrode plate is 95% by weight of graphite, 2% by weight of conductive SP, and 2% by weight of CMC. After the steps of baking, rolling, die-cutting, roll welding, lamination, spot welding, plastic film forming, liquid injection, formation, and volume separation, the 1AH soft-pack battery cell is prepared. The size of the positive and negative electrode plates after die-cutting is 42mm×54mm for the positive electrode and 44mm×56mm for the negative electrode, and the number of lamination layers is 10 for the positive electrode and 11 for the negative electrode. The roll welding parameters are consistent with those in the above roll welding performance test. The positive electrode of the conventional battery cell is electrolytic copper foil, and the negative electrode is rolled aluminum foil. The 1AH soft-pack battery cell is also prepared by lamination. The battery cell prepared above was charged and discharged at 3C and 1C at 25°C to obtain the cycle charge and discharge results. The test results are shown in Table 3. The 1C charge and discharge cycle performance test results of Example 1 and Comparative Examples 1-2 are shown in Table 3. Figure 7 As shown, the 3C charge-discharge cycle performance test results of Example 1 and Comparative Examples 1-2 are as follows Figure 8 shown.

[0258] Table 3

[0259]

[0260] From the comparison of the results of Examples 1-11 and Comparative Examples 1-4 in Table 3, it can be seen that the capacity retention rate of Examples 1-11 after 1000 cycles is significantly better than that of Comparative Examples 1-4; and the capacity retention rate of Comparative Example 2 after 1000 cycles is better than that of Comparative Example 1. This shows that the cyclic charge and discharge performance of the lithium battery cell finally prepared is improved by partitioning the polypropylene base film, and the conductive coating plays a major role in improving the cyclic charge and discharge performance.

[0261] By comparing the results of Examples 10-11 and Comparative Example 4, it can be seen that when the length of the projection of the adapter on the modified layer accounts for 60%-100% of the coating width of the conductive coating area, the risk of tearing of the conductive layer due to pulling of the adapter during welding is reduced by increasing the welding contact area of ​​the adapter, thereby effectively avoiding the problem of decreased battery rate performance.

[0262] 6. The base films in Examples 1-11 and Comparative Examples 1-4 were prepared into composite current collectors, and the internal resistance of the electrode sheets was tested after copper foil roll welding.

[0263] The preparation method of the composite current collector is the same as the preparation method of the composite current collector in 2 above. The negative electrode sheet is prepared according to the preparation method of the negative electrode sheet recorded in 5, and the internal resistance at points ① and ② is measured using an internal resistance tester. The size of the electrode sheet is (L×D: 44mm×56mm), and the distance from ② to the upper end is 20mm. When testing the internal resistance, the graphite layer at point ② is removed to expose the metal layer. The schematic diagram of the test point is as follows Fig. 9 The test results are shown in Table 4.

[0264] Table 4

[0265] Group Internal resistance(mΩ) Example 1 1.4 Example 2 1.6 Example 3 1.7 Example 4 1.3 Example 5 1.4 Example 6 1.5 Example 7 1.2 Example 8 1.3 Example 9 1.4 Example 10 1.3 Embodiment 11 1.2 Comparative Example 1 3.6 Comparative Example 2 3.8 Comparative Example 3 1.4 Comparative Example 4 1.8

[0266] From the comparison of the results of Example 1-11 and Comparative Example 1-4 in Table 4, it can be seen that the internal resistance of the negative electrode sheet prepared in Example 1-11 is quite different from that of the negative electrode sheet prepared in Comparative Examples 1-2 and 4, and the overall internal resistance of the negative electrode sheet prepared in Example 1-11 is significantly lower than that of the negative electrode sheet prepared in Comparative Examples 1-2 and 4; indicating that the conductivity of the composite current collector can be significantly improved and the internal resistance of the negative electrode sheet can be reduced by modifying the conductive coating.

[0267] From the comparison of the results of Examples 10-11 and Comparative Example 4, it can be seen that when the projection length of the adapter on the modified layer accounts for 60%-100% of the coating width of the conductive coating area, it is beneficial to reduce the internal resistance of the negative electrode plate.

[0268] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0269] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A modified base film, characterized in that: include: basement membrane body; and A modified layer is located on at least one side surface of the base film body, the modified layer includes an adhesion modification area and a conductive coating area, the coating width of the adhesion modification area along the first direction is the same as the coating width of the conductive coating area along the first direction, the coating width of the conductive coating area along the second direction is 1.5cm-2.5cm, the first direction and the second direction are respectively parallel to the two adjacent edges of the base film body; when the modified base film is used in an electrode, the projection of the active material layer on the modified layer is located in the adhesion modification area, and the projection of the adapter on the modified layer is located in the conductive coating area.

2. The modified base film according to claim 1, characterized in that The adhesion modification region and two adjacent edges of the conductive coating region are connected by a connector, and the material of the connector includes at least one of aluminum oxide, titanium dioxide, silicon dioxide and zinc oxide.

3. The modified base film according to claim 1, characterized in that The adhesion-modified region comprises one or more of a binder, a curing agent, a dispersant, a coupling agent, and a lubricant; Optionally, the mass ratio of the binder to the curing agent is (20-40):(3-7); Optionally, the mass ratio of the binder to the dispersant is (20-40):(3-7); Optionally, the mass ratio of the binder to the coupling agent is (20-40):(1-5); Optionally, the mass ratio of the binder to the lubricant is (20-40):(1-5); Optionally, the binder includes one or more of polymethyl methacrylate, carboxymethyl cellulose, modified epoxy resin, polyethylene-polypropylene copolymer and polyurethane; Optionally, the curing agent includes one or more of N,N-dimethylformamide, polyamide, dicyandiamide and maleic anhydride; Optionally, the dispersant includes one or more of hydroxypropyl methylcellulose, glycidyl butyl ether, polycarboxylic acid amine and polyamine polyamide salt; Optionally, the coupling agent includes one or more of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane and vinyltriethoxysilane; Optionally, the lubricant includes one or more of silicone oil, alkyd resin, polyvinyl alcohol and silicate.

4. The modified base film according to claim 1, characterized in that The conductive coating region comprises one or more of a base resin, a conductive filler and an additive; Optionally, the mass ratio of the matrix resin to the conductive filler is (20-85):(2-70); Optionally, the mass ratio of the base resin to the auxiliary agent is (20-85):(1.5-3.5); Optionally, the matrix resin includes one or more of thermoplastic acrylic resin, polyurethane resin, epoxy resin, polystyrene butadiene resin, silicone resin, alkyd resin and modified resins corresponding to the above resins; Optionally, the auxiliary agent includes one or more of an initiator, a wetting agent, a defoaming agent and a coupling agent; Optionally, the conductive filler comprises one or more mixtures of metal conductive fillers, carbon conductive fillers, non-metal conductive fillers and conductive polymer fillers; Further optionally, the metal-based conductive filler includes one or more of Ag, Ni and Cu; Further optionally, the carbon-based conductive filler includes one or more of carbon black, graphite, graphene, carbon nanotubes and carbon fibers; Further optionally, the non-metallic conductive filler includes one or more of tin oxide, zinc oxide, antimony dioxide and titanium dioxide; Further optionally, the conductive polymer filler includes one or more of polyaniline, polypyrrole, polythiophene, and poly(3,4-ethylenedioxythiophene) polystyrene sulfonate.

5. The modified base film according to any one of claims 1 to 4, characterized in that: The coating thickness of the modified layer along the third direction is 260nm-340nm, and the third direction is perpendicular to the first direction and the second direction respectively; and / or The material of the base film body includes polypropylene.

6. A method for preparing a modified base film, characterized in that: The preparation method comprises the following steps: Coating a modified adhesive slurry on a partial area of ​​at least one side of the surface of the base film body and coating a conductive coating on a partial area to prepare an adhesion modified area and a conductive coating area respectively to form a modified layer; Drying the base film body after forming the modified layer; Among them, the coating width of the adhesion modified area along the first direction is the same as the coating width of the conductive coating area along the first direction, the coating width of the conductive coating area along the second direction is 1.5cm-2.5cm, and the first direction and the second direction are respectively parallel to the two adjacent edges of the base film body; when the modified base film is used in the electrode, the projection of the active material layer on the modified layer is located in the adhesion modified area, and the projection of the adapter sheet on the modified layer is located in the conductive coating area.

7. The preparation method according to claim 6, characterized in that: Before the step of drying the base film body after forming the modified layer, the method further comprises: Filling bonding material between two adjacent edges of the bonding force modified region and the conductive coating region; Optionally, the bonding material includes one or more of aluminum oxide, titanium dioxide, silicon dioxide and zinc oxide.

8. The preparation method according to claim 6, characterized in that: The modified adhesive slurry comprises a binder, a curing agent, a dispersant, a coupling agent, a lubricant and a solvent A; Optionally, the binder accounts for 20%-40% by mass in the modified binder slurry; Optionally, the mass proportion of the curing agent in the modified adhesive slurry is 3%-7%; Optionally, the mass proportion of the dispersant in the modified binder slurry is 3%-7%; Optionally, the coupling agent accounts for 1% to 5% by mass in the modified adhesive slurry; Optionally, the mass proportion of the lubricant in the modified adhesive slurry is 1%-5%; Optionally, the solvent A comprises ethylene glycol; and / or The conductive coating comprises a base resin, a conductive filler, an additive and a solvent B; Optionally, the mass proportion of the matrix resin in the conductive coating is 20%-85%; Optionally, the conductive filler accounts for 2%-70% by mass in the conductive coating; Optionally, the mass percentage of the auxiliary agent in the conductive coating is 1.5%-3.5%; Optionally, the auxiliary agent includes one or more of an initiator, a wetting agent, a defoaming agent and a coupling agent; Optionally, the solvent B includes one or more of toluene, ethanol, acetone, xylene, cyclohexane, cyclohexanone, ethyl acetate, n-butanol, isopropanol, dimethylformamide and butyl acetate.

9. The preparation method according to claim 6, characterized in that: Before the step of preparing the modified layer, the method further includes: plasma cleaning the base film body; Optionally, the cleaning gas for plasma cleaning includes argon; Optionally, the power of the plasma cleaning is 110W-180W; Optionally, the plasma cleaning time is 6s-10s; Optionally, the bias voltage of the plasma cleaning is 400V; Optionally, the gas flow rate of the plasma cleaning is 400 sccm.

10. The preparation method according to any one of claims 6 to 9, characterized in that: The step of drying the base film body after forming the modified layer comprises: Sequentially performing far-infrared radiation heating drying and oven drying on the base film body after forming the modified layer; Optionally, the infrared band used in the far-infrared radiation heating drying is 3 μm-14 μm; Optionally, the maximum power density of the far-infrared radiation heating drying is 3W / cm 2 -5W / cm 2 ; Optionally, the drying time of the far-infrared radiation heating drying is 1 min-3 min; Optionally, the oven drying temperature is 60°C-100°C; Optionally, the oven drying time is 1 min-3 min.

11. A composite current collector, characterized in that: It comprises a modified base film and a metal layer located on at least one side of the surface of the modified base film; the modified base film adopts the modified base film described in any one of claims 1 to 5 or a modified base film prepared by the preparation method described in any one of claims 6 to 10.

12. An electrode, characterized in that: It includes a composite current collector as described in claim 11 and an active material layer and a transfer sheet located on at least one side surface of the composite current collector, wherein along the second direction, the length of the projection of the transfer sheet on the modified layer accounts for 60%-100% of the coating width of the conductive coating area, and the transfer sheet does not contact the active material layer.

13. The electrode according to claim 12, characterized in that The distance between the edge of the adapter sheet adjacent to the adhesion modification region and the edge of the conductive coating region adjacent to the adhesion modification region is 0-12 mm.

14. A battery cell, characterized in that: Comprising the electrode according to any one of claims 12 to 13.

15. An electrical device, characterized in that: Comprising the battery cell as claimed in claim 14.

Citation Information

Cited By

  • High-strength PP base film and preparation method thereof

    CN120842656A

  • Composite film and preparation method and application thereof

    CN120902387A